2018
DOI: 10.1007/s11897-018-0397-5
|View full text |Cite
|
Sign up to set email alerts
|

Decompensated Heart Failure and Renal Failure: What Is the Current Evidence?

Abstract: One of the strongest predictors of adverse outcomes in ADHF is renal dysfunction, referred to as cardiorenal syndromes (CRS) or cardiorenal interactions. Patients with ADHF frequently develop worsening of renal function (WRF) and/or acute kidney injury (AKI). Recent studies brought new information about biomarkers in diagnosing and predicting prognosis of CRS. Among others, dry weight at hospital discharge is considered a surrogate marker of successful treatment in ADHF patients with/without renal dysfunction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
11

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 110 publications
1
15
0
11
Order By: Relevance
“…Patients admitted to hospital with heart failure commonly have some degree of renal dysfunction. [25] Worsening renal function is one of the most important prognostic variables in heart failure patients. [26] The impaired renal clearance and upregulation of xanthine oxygenase can be responsible for elevated uric acid level.…”
Section: Discussionmentioning
confidence: 99%
“…Patients admitted to hospital with heart failure commonly have some degree of renal dysfunction. [25] Worsening renal function is one of the most important prognostic variables in heart failure patients. [26] The impaired renal clearance and upregulation of xanthine oxygenase can be responsible for elevated uric acid level.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with HF, the incidence and impact of AKI have been reported mainly in subjects hospitalized with acute HF (AHF), in which the prevalence of AKI is ~20%, and it has been recognized that AKI is a strong independent predictor of both in‐hospital and 1‐year mortality . A meta‐analysis of cohorts, registries, and post‐hoc studies concluded that CKD and worsening of renal function (WRF), a term that has been used instead of AKI in HF patients, are frequently observed in patients with HF. However, the authors acknowledge heterogeneity due to different inclusion criteria, selection bias, and different definitions and criteria used to qualify AKI .…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal reflux, duodenal ulcers, and angiodysplasia occur in more than 30% of this aged population [8,20]. In addition, patients with HF are at risk of developing AKI [21], due to a low cardiac output or congestive status, as well as the use of drugs blocking the renin-angiotensin system or diuretics. In an AKI condition, Hb falls is an accompanying element [21], mainly in the most severe classes, and increase the burden to the heart [18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients with HF are at risk of developing AKI [21], due to a low cardiac output or congestive status, as well as the use of drugs blocking the renin-angiotensin system or diuretics. In an AKI condition, Hb falls is an accompanying element [21], mainly in the most severe classes, and increase the burden to the heart [18]. Whether the incidence of hospitalization or mortality was higher in patients with a reduced left ventricular ejection fraction than in those with a preserved ejection fraction was not possible to assess in the present study, due to the low number of left ventricular functions recorded in the EHR.…”
Section: Discussionmentioning
confidence: 99%